Effect of Room and High Temperature Compaction on Optical and Mechanical Properties of HIPed Transparent Spinel Ceramics . Issue 8 (26th April 2017) - Biswas, Papiya; Ramavath, Pandu; Kumbhar, Chandrashekhar Sadasiv; Patil, Dinesh S.; Chongdar, Tapas Kumar; Gokhale, Nitin Madhusudan; Johnson, Roy; Mohan, Mantravadi Krishna
Abstract : Spinel specimens are processed through Hot Pressing at 1620 °C and 20 MPa (designated as HPS) and uniaxial pressing at room temperature with 80 MPa followed by pressure‐less sintering at 1650 °C (designated as CS). HPS exhibit translucency with marginally higher density (99.8% of theoretical density (TD)) in comparison to CS with 99.5% of TD and negligible transmission value. HPS samples have shown a transmission of 40 and 76% in visible and midwave infrared (MWIR) region, respectively. Both HPS and CS samples are further subjected to Hot Isostatic Pressing (designated as HPS + HIP and CS + HIP, respectively), at identical conditions of 1800 °C and 195 MPa to achieve close to TD and transparency. HPS + HIP and CS + HIP samples enhance their transmission to 78 and 71% in visible region and 86 and 79% in MWIR region, respectively. Although most important parameter for transparent ceramics, i.e., transmission values are relatively high for HPS + HIP samples and exhibit substantially lower hardness and flexural strength values in comparison to CS + HIP samples at room and elevated temperature. Fractographic studies of samples fail under flexure at room and elevated temperature have exhibited cleavage fracture with longer facet length for HPS + HIP correlating well with microstructure. Difference in mechanical properties can be attributed to differences in grain size produced by two methodologies. Abstract : MgAl2 O4 spinel powder compacted under room and elevated temperature, are subjected to hot isostatic pressing followed by property evaluations. Though the samples, processed through both the routes have identical densities, mechanical properties are superior for cold compacted samples in comparison to hot compacted samples which have exhibits better optical transmission. Results are also correlated with processing conditions.